SCREENING OF SOME LONG DURATION GENOTYPES OF TION GENOTYPES OF PIGEONPEA [ PIGEONPEA [Cajanus cajan (L.) Millisp.] AGAINST THE INFESTATION OF POD FLY [Melanagromyza obtusa Melanagromyza obtusa (Malloch)] (Malloch)] - SITANSHU, SABUJ GANGULY, C. P. SRIVASTAVA AND (The Bioscan, 2018)
The present investigation was carried out to screen twenty-five long duration genotypes of pigeonpea, Cajanus cajan (L.) Millsp. against pod fly, Melanagromyza obtusa (Malloch) at the Agricultural Research Farm of Institute of Agricultural Sciences, Banaras Hindu University, Varanasi during kharif, 2014-15. The pest marked its first appearance during 4th standard week and recorded highest mean maggot population in genotype ICPL 84060-1 (1.3 maggots /plant) followed by T-21 (1.2 maggots /plant), ICPHaRL 4979-2 (1.1 maggots /plant), Bahar (check) (1.0 maggots /plant) and lowest in genotype ICP 7035-1 and ICPHaRL 4987-11 (0.2 maggots /plant) followed by genotype ICPHaRL 4989-7, ICPL 88039-1 and ICPX 77303 (0.3 maggots / plant) in the population dynamics study. The per cent pod damage and grain damage due to pod fly on different pigeonpea genotypes differed significantly and ranged from 19.5 per cent in genotype ICP 7035-1 to 54.0 per cent in genotype ICPL 84060-1 and 6.82 per cent in genotype ICP 7035-1 to 26.72 per cent in genotype ICPL 84060-1 respectively. Due to the adverse weather conditions, very low grain yields were recorded but they differed significantly and ranged from 105.6 kg/ha in the genotype ICPL 85063 to 338.9 kg/ha in ICP 7035-1. Genotype ICP 7035-1 performed best in comparison to other genotypes against pod fly infestation.